Ethics and Leadership in Crisis Management: A Systematic Literature Review - Dwinanda, Rizky Ridho; Utama, Anak Agung Gde Satia; Fauziyan, Ali (Jurnal Ilmiah Manajemen & Bisnis, 2025)
This study aims to systematically examine the role of ethical leadership in enhancing crisis management outcomes across various sectors, focusing on significant global crises such as the COVID-19 pandemic and the 2007–2009 financial crisis. Employing a systematic literature review guided by PRISMA protocols, six peer-reviewed articles from high-impact journals were analyzed using thematic content analysis. Key findings reveal that ethical leadership substantially improves both immediate crisis responses and long-term organizational resilience by fostering transparency, accountability, and stakeholder trust. Leadership styles, including transformational, directive, and responsible leadership, when integrated with robust ethical frameworks, effectively navigate complex crisis challenges while mitigating adverse effects on employees and reputation. The study underscores the importance of ethical communication and inclusive decision-making in sustaining organizational legitimacy during crises. Practical implications suggest that organizations should embed ethical leadership in crisis preparedness strategies and prioritize employee well-being during restructuring. The study contributes to the scholarly body by highlighting the necessity of sector-specific ethical frameworks and calling for more interdisciplinary, longitudinal research to deepen understanding ethical leadership in crisis contexts.